THE ETHNO-CONFESSIONAL ASPECT OF THE MONTAGUE-CHELMSFORD REFORM IN BRITISH INDIA. - Sagimbayev A.V. (Вестник Брянского государственного университета)
The article examines the main aspects of administrative and political transformations in British India at the turn of the 1910s - 1920s in the context of the processes of development of the national liberation movement, as well as ethno-political consolidation in certain Indian regions. The interwar period was marked by a significant transformation of the British colonial system, which affected, among other things, the management mechanisms of Indian possessions. Implemented on the basis of the law adopted in December 1919 . By a special legislative act of the British Parliament, the administrative and political reform, which went down in history as the Montague-Chelmsford reforms, was an attempt to modernize the management system in a key colony. At the same time, this reform, as well as the subsequent transformations carried out by the colonial administration, contributed to the formation of elements of the political culture of Indian society, and also, to a certain extent, laid the foundations of the future federal system of independent India.